Validation of a Classroom Management Questionnaire for pre and Inservice Teachers of English - Claudio Díaz; Georgina González; Lucas Ignacio Jara-Ramírez; Javiera Alejandra Muñoz-Parra (Revista Colombiana de Educación, 2018)
Classroom management is a permanent concern and challenge for teachers. Good classroom management practices are critical to facilitate effective learning and therefore, researchers are continuously exploring ways to measure this construct from different perspectives. Questionnaires are one of the tools used to gather relevant data. This article presents an approach to the validation of a classroom management questionnaire. To validate this questionnaire, items were assessed by experts in the field through the application of two member checking techniques, namely, Delphi and Fleiss’ Kappa that implied a series of changes in some of the items. Finally, a small pilot testing conducted among pre and in-service teachers of English yielded an excellent Cronbach’s Alpha, resulting in a highly reliable questionnaire.